Rekognisi Agama Lokal Prasyarat Menuju Demokrasi Majemuk - Sudarto Sudarto (Tamaddun, 2019)
The biggest challenge for plural democracy is how to manage the diversity of its people according to the principles of equality and justice. In this connection, it cannot be denied Indonesia as a plural state is being faced with the maturation of democracy on one side, and the challenges of managing the diversity of its people on the other side. Some of the challenges of pluralism that still occur in Indonesia include: First, there are still many overlapping regulations. Especially regarding the management of religious diversity. Secondly, law enforcers do not provide protection. Mainly related to freedom of religion or belief. Third, although Indonesian people basically live in a pluralistic reality, but in fact the foundation of tolerance of the plural Indonesian society is still relatively fragile. The problem of managing the diversity of religions or beliefs as described above, has an interconnected relationship with the difficulty of presenting the moderation of religions in Indonesia. The question is how to manage the diversity of religions and beliefs according to the principle of equality and fairness, especially for the local belief groups of the archipelago, which in political language is called the flow of trust nomenclature? How is the portrait of the state's treatment of local religious groups? And offers the concept of diversity management which is expected to contribute to reaffirming Indonesia's diversity towards Islamic moderation. Because it cannot be denied, speaking of religious moderation actually speak of religious tolerance amid diversity in high intensity.